Resorbable elastomers for implantable medical devices: highlights and applications - Turner, B.; Ramesh, S.; Menegatti, S.; Daniele, M.
Resorbable elastomers are an emerging class of materials required for transient implantable medical devices (IMDs), as their tissue-matching mechanical properties decrease the risks associated with implant removal and promote functional tissue integration. Traditional materials employed in IMDs are typically much more rigid than native tissue, which leads to increased foreign body response and tissue irritation, and must be removed at the end of life of the implant, thus increasing the risk to patients. Resorbable elastomeric biomaterials support efficiently all the functions of substrate/encapsulant, dielectric, semiconductors and conductors that are needed in IMDs, while offering beneficial mechanical properties and a programed degradation that circumvents the need for surgical removal. This mini-review presents the chemical characteristics, material properties and applications as IMD substrates of three resorbable elastomer families: polyurethane, poly(glycerol sebacate)and poly(diol citrate). Finally, some challenges and future directions on the pathway to biomedical adoption of resorbable elastomeric biomaterials are discussed including safety, processing conditions and critical development steps for conductive and dielectric elastomers. © 2021 Society of Industrial Chemistry.
Keywords: ELASTOMERS; IMPLANTABLE MEDICAL DEVICES; RESORBABLE; BIOELECTRONICS